Participationto the Conflict Managementin Wat Noi Nang Hong Community, Singburi Province - Anando, Phramaha Khittithanade; Dhammahaso, Phramaha Hunsa (Journal of International Buddhist Studies, 2016)
This article is intended to present the application of Buddhist participation to the conflict management in Wat Noi Nang Hong Community, Singburi Province. Information is gathered from the evidence of participation in Buddhist perspective in the theory parts, according to the guideline of the west. In-depth interview. To observe and listening to public opinions, people in involved in Wat Noi Nang Hong community. From the research, it is found that the study related to the application of the ideas and principles of the participation in Buddhist perspective to manage conflicts and create community’s unity, it is also found that the community leaders in the present lack virtues which are the tools of having trusts from people in the community. Hence, in order to bring back community leaders to have the equal roles comparing to the ones in the past, there must be the application of the Dhammas of the leaders in the past to let them have the roles in the aspects of “having the right view; acting as trustful relatives with the holy Dharma of Brahmavihara (The four divine abodes); and being able to make friendship by self-controlling with Sangahavatthu Dhamma”. Therefore, there must be use of the process of the participation in Buddhist perspective as the impulsion for the movement of people’s or private sector; it is divided into the 2 models of (1) the 5-Step-Model of the Participation in Buddhist Perspective (R5 Steps); and (2) the Process Model of the Participation in Buddhist Perspective (Noble Eightfold Cycle), both of which consist of the harmonization of “the Noble Eightfold Path or Magga”, the important principle for the movement of sustainable participation in Buddhist perspective.